Pediatric first aid, CPR, and AED (McGraw-Hill, 2006)
The Pediatric First Aid, CPR & AED manual is 153 pages and full-color. It covers the material included in a 6 to 7.5-hour course. This book is for anyone who takes care of children, including parents, daycare and other childcare workers, teachers and others. The focus is on preventing childhood injury where possible, how to recognize and act in a pediatric emergency and sustain life until professional help can arrive. Along with basic first aid components such as bleeding control and shock, the book covers child abuse and common childhood illnesses.